2020
DOI: 10.3390/nano10081545
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Manganese Dioxide Nanosheets by ROS-Mediated Pathways and Destroying Membrane Integrity

Abstract: Manganese dioxide (MnO2) nanosheets have shown exciting potential in nanomedicine because of their ultrathin thickness, large surface area, high near-infrared (NIR) absorbance and good biocompatibility. However, the effect of MnO2 nanosheets on bacteria is still unclear. In this study, MnO2 nanosheets were shown for the first time to possess highly efficient antibacterial activity by using Salmonella as a model pathogen. The growth curve and surface plate assay uncovered that 125 μg/mL MnO2 nanosheets could ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…CuNPs are also well known to be highly cytotoxic by the release of ions and the production of ROS [59]. Additionally, other MONPs, such as ZnO [60], TiO 2 [61], and MnO [62], have been proven to exhibit bactericidal activity via their ability to stimulate the cell to produce ROS (Figure 1). In addition to the disruption of bacterial membranes, NPs have been demonstrated to disrupt biofilm formation.…”
Section: Metal-based Nanoparticles Target Ros Production In Bacteriamentioning
confidence: 99%
“…CuNPs are also well known to be highly cytotoxic by the release of ions and the production of ROS [59]. Additionally, other MONPs, such as ZnO [60], TiO 2 [61], and MnO [62], have been proven to exhibit bactericidal activity via their ability to stimulate the cell to produce ROS (Figure 1). In addition to the disruption of bacterial membranes, NPs have been demonstrated to disrupt biofilm formation.…”
Section: Metal-based Nanoparticles Target Ros Production In Bacteriamentioning
confidence: 99%
“…In the present study, F@Ce6‐M could decompose H 2 O 2 into O 2 , thus boosting the generation of ROS. Moreover, it has been suggested that MnO 2 nanostructure also have highly effective antibacterial activity, [ 43 ] because of the production of ROS, the increase of ATPase activity, the leakage of protein contents and electrolytes. On the basis of single bacteria level experiments, the F@Ce6‐M NCs exerted its enhanced antibacterial effect on the disruption of the biofilm by increasing local oxygen tension.…”
Section: Resultsmentioning
confidence: 99%
“…The energy difference between the two peaks is 11.7 eV, indicating that Mn 4+ in MnO X is the main oxidation state of Mn 41,44 . MnO 2 can induce the production of Please do not adjust margins Please do not adjust margins ROS, increase the activity of ATPase and cause the leakage of electrolyte and protein content, leading to the death of bacteria 45 .…”
Section: Resultsmentioning
confidence: 99%